Moving Toward Non-transcription based Discourse Analysis in Stable and Progressive Aphasia - Dalton, Sarah Grace Hudspeth; Hubbard, H. Isabel; Richardson, Jessica D. (Seminars in Speech and Language, 2020)
Measurement of communication ability at the discourse level holds promise for predicting how well persons with stable (e.g., stroke-induced), or progressive aphasia navigate everyday communicative interactions. However, barriers to the clinical utilization of discourse measures have persisted. Recent advancements in the standardization of elicitation protocols and the existence of large databases for development of normative references have begun to address some of these barriers. Still, time remains a consistently reported barrier by clinicians. Non-transcription based discourse measurement would reduce the time required for discourse analysis, making clinical utilization a reality. The purpose of this article is to present evidence regarding discourse measures (main concept analysis, core lexicon, and derived efficiency scores) that are well suited to non-transcription based analysis. Combined with previous research, our results suggest that these measures are sensitive to changes following stroke or neurodegenerative disease. Given the evidence, further research specifically assessing the reliability of these measures in clinical implementation is warranted.
Keywords: transcription; discourse; aphasia; clinical utility